2021
DOI: 10.1039/d1cc00223f
|View full text |Cite
|
Sign up to set email alerts
|

Resorcin[4]arene-based multidentate phosphate ligands with superior binding affinity for nanocrystal surfaces

Abstract: We synthesized two resorcin[4]arene scaffolds with four phosphate binding groups. The superior binding affinity to nanocrystal surfaces is demonstrated using solution NMR spectroscopy and exceeds that of single phosphonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…We installed four phosphates either on the top or the bottom rim; see Figure 10. 101 By carefully titrating oleate capped zirconia nanocrystals with the macrocyclic ligands, we found that both our macrocycles are at least tridentate (possibly tetradentate) at low ligand coverage. However, the macrocyclic ligands need three/four adjacent free binding sites to bind according to its maximal denticity.…”
Section: Ligand Design Toward High Binding Affinitymentioning
confidence: 84%
“…We installed four phosphates either on the top or the bottom rim; see Figure 10. 101 By carefully titrating oleate capped zirconia nanocrystals with the macrocyclic ligands, we found that both our macrocycles are at least tridentate (possibly tetradentate) at low ligand coverage. However, the macrocyclic ligands need three/four adjacent free binding sites to bind according to its maximal denticity.…”
Section: Ligand Design Toward High Binding Affinitymentioning
confidence: 84%
“…In addition to proton transfer, other factors also play a role in an X-type exchange. Steric bulk can hamper ligand exchange, multidentate ligands feature enhanced binding affinity, and the ligand solubility can also steer the exchange reaction. , The binding enthalpy of an X-type ligand can be particularly high for certain surfaces but low for other surfaces due to chemical compatibility. For example, thiols have a high affinity for the surface of metal chalcogenide or metallic NCs but are generally poor ligands for metal oxides. ,,,, Finally, a ligand exchange reaction can be forced by the formation of energetically favorable byproducts.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21] Phosphonates and phosphates are among the strongest ligands available and easily displace carboxylic acids, 13,[22][23] especially when designed as multidentate ligands on a scaffold. [24][25] Phosphonic acids are also the ligands of choice for high temperature (> 300 °C) quantum dot syntheses. Peng et al used a mixture of saturated phosphonic acids to synthesize CdE (E = S, Se or Te) NCs and nanorods.…”
Section: Introductionmentioning
confidence: 99%
“…Metal oleates are stable metal precursors for quantum dot syntheses at relatively low temperatures (240 °C). , At higher temperatures they often decompose to metals or metal oxides. , Oleylamine is a typical L-type ligand and usually binds in a dynamic fashion . In very specific systems, oleylamine can be a tightly bound ligand. , Phosphonates and phosphates are among the strongest ligands available and easily displace carboxylic acids, ,, especially when designed as multidentate ligands on a scaffold. , Phosphonic acids are also the ligands of choice for high-temperature (>300 °C) quantum dot syntheses. Peng et al used a mixture of saturated phosphonic acids to synthesize CdE (E = S, Se, or Te) NCs and nanorods .…”
Section: Introductionmentioning
confidence: 99%